2013
DOI: 10.1177/1350506812471338
|View full text |Cite
|
Sign up to set email alerts
|

Silent bodies: Childfree women’s gendered and embodied experiences

Abstract: This article reports from the first studies on voluntary childlessness in Sweden and addresses a so far neglected issue -the embodied experiences of childfree women. These childfree women reject and resist pronatalist understandings that conflate being a woman with being a mother. However, instead of explaining their childlessness by external factors, mentioned in previous research, the interviewed women created a positive feminine identity separated from motherhood with reference to their 'silent bodies', i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
3
38
0
8
Order By: Relevance
“…Studies using a qualitative approach have identified a wide range of different motivators for women, such as; lack of "maternal instinct"; dislike of, or disinterest in, children; fear of painful childbirth; humanitarian concerns about population growth; career orientation, and; a more satisfactory marriage (Callan, 1986;Park, 2005;Peterson & Engwall, 2013;Somers, 1993;Veevers, 1980). The most frequently mentioned benefit of remaining childless is the feeling of freedom it affords (Houseknecht, 1987).…”
Section: Previous Research On Voluntary Childlessnessmentioning
confidence: 98%
“…Studies using a qualitative approach have identified a wide range of different motivators for women, such as; lack of "maternal instinct"; dislike of, or disinterest in, children; fear of painful childbirth; humanitarian concerns about population growth; career orientation, and; a more satisfactory marriage (Callan, 1986;Park, 2005;Peterson & Engwall, 2013;Somers, 1993;Veevers, 1980). The most frequently mentioned benefit of remaining childless is the feeling of freedom it affords (Houseknecht, 1987).…”
Section: Previous Research On Voluntary Childlessnessmentioning
confidence: 98%
“…Establishing exactly which policies that can achieve an increase in fertility is beyond the scope of this paper. What can be concluded is that a wide range of motivators influences such a life decision as remaining childless, some of which are related to social, cultural, economical, political and gender-specific pre-conditions (Peterson 2014b;Peterson and Engwall 2013).…”
Section: Concluding Discussionmentioning
confidence: 96%
“…Voluntary childlessness has been and still is seen as a sign of immaturity or selfishness, and childless women are often seen as “psychologically maladjusted, emotionally immature, immoral, selfish, lonely, unhappy, unfulfilled, sexually inadequate, unhappily married, and prone to divorce” (Veevers , 7), “deviant,” “aberrant, immature, and unfeminine” (Gillespie , 225; Letherby , 10). Such negative perceptions of childless women may have subsided to some extent in some environments but are still shared today (Vinson, Mollen, and Smith ; Peterson and Engwall ). Failure to reproduce is questioned, and “[p]eople keep asking childless women why they are childless, whether they plan to remain childless, how they feel about being childless, and they warn them that they are going to be lonely in their old age” (Stotland in Rhodes ).…”
Section: Encouraging a Pro‐reproductive Culture And Never Giving Upmentioning
confidence: 99%